The Existence of Culture and Social Community of the Paksi Pak Skala Brak Kepaksian Bejalan Diway Kingdom in Kembahang Village from 1999 to 2025 - Arisca, Naufal; Setiawati, Elis; Hartati, Umi; Afwan, Bahtiar (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The purpose of this study is to explore the history and development of the Kepaksian Bejalan Diway Kingdom, analyze the role of traditional leaders in implementing social life, examine the relationship between Belasa Kepampang and the culture of the Lampung Sai Batin community, and reveal the key factors behind the persistence of cultural and social life in the Paksi Pak Sekala Brak Traditional Kingdom.The research method used was descriptive qualitative, with data collection techniques including observation, documentation, literature studies, and interviews with traditional leaders and the Kembahang Village community. The findings show that the Kepaksian Bejalan Diway Kingdom is part of the Paksi Pak Sekala Brak Kingdom, which continues to uphold its customs to this day. Its history traces back to the transformation of the Hindu Sekala Brak Kingdom into the Islamic Kepaksian Kingdom following the arrival of four umpu from Pagaruyung.The role of traditional leaders is crucial in maintaining social harmony through the practice of Piil Pesenggiri values, such as Juluk Adek, Nemui Nyimah, Nengah Nyappur, and Sakai Sambayan. The relationship with Belasa Kepampang reflects the interconnectedness of local beliefs and the formation of the Sai Batin community's cultural identity. The primary factors sustaining the kingdom's existence are the community’s adherence to tradition, strong communication among the various kingdoms, and collective awareness of preserving ancestral culture.